AGENT BASED MONITORING FRAMEWORK FOR SERVICE LEVEL AGREEMENTS IN SERVICE ORIENTED ARCHITECTURE ENVIRONMENTS - AHMED BALFAQIH, ZAIN ABOBAKR (2013)
In the current implementation of SOA using web services, in which different services can provide the same functionality for consumers, Quality of Services (QoSs) become essential in determining the most suitable services for consumers. These qualities arc normally described in the service level agreement (SLA) between the consumers and providers. An SLA is developed between two parties to formally specify who is responsible for what. what each party will do. and sometimes more importantly what each party will not do.